EFFECTIVENESS OF LEARNING WITH INTERACTIVE MULTIMEDIA TO IMPROVE LEARNING OUTCOMES USING THE COMMAND FUNCTION IN MAKING 3D CAD DRAWINGS - Alvin Maulana Al Bahri; Ari Dwi Nur Indriawan Musyono; Dwi Widjanarko; Sudiyono (Jurnal Pendidikan Teknik Mesin, 2023)
The SMK learning process should direct students to have insight into the world of business or industry, one of which is CAD-based Manufacturing Engineering Drawing subject skills, but it turns out that student learning outcomes are known under the KKM. The aims of this study were to find out 1) the feasibility of interactive multimedia according to media and material experts 2) students' perceptions of the usefulness of interactive multimedia 3) the effectiveness of interactive multimedia to improve learning outcomes. This study used a quantitative approach to numerical data with the One-Group Pretest-Posttest design. involving control and experimental groups. The population of class XI machining students at SMKN1 Losarang. Samples of XITP 1 and XITP 2 students. The pretest results mean 56.99, median 56 mode 50 standard deviation 13.93. The posttest mean 81.86, median 83 mode 86 standard deviation 7.01, there is an increase in posttest scores due to the effect of interactive multimedia on students easily practicing 3D CAD drawings. Conclusion 1) Interactive multimedia learning to make 3D CAD drawings is considered quite feasible by media experts and appropriate by material experts 2) Students' perceptions of interactive Multimedia learning to make CAD drawings are considered quite useful 3) Student learning outcomes after using interactive multimedia in making 3D CAD drawings considered effective.